Primary care blood tests show lipid profile changes in pre-symptomatic amyotrophic lateral sclerosis - Thompson, AG; Marsden, R; Talbot, K; Turner, MR (Oxford University Press, 2023)
Multiple sources of evidence suggest that changes in metabolism may precede the onset of motor symptoms in amyotrophic lateral sclerosis. This study aimed to seek evidence for alterations in the levels of blood indices collected routinely in the primary care setting prior to the onset of motor symptoms in amyotrophic lateral sclerosis. Premorbid data, measured as part of routine health screening, for total cholesterol, high-density and low-density lipoprotein cholesterol, triglyceride, glycated haemoglobin A1c and creatinine were collected retrospectively from (i) a cohort of amyotrophic lateral sclerosis patients attending a specialist clinic (n = 143) and (ii) from primary care-linked data within UK Biobank. Data were fitted using linear mixed effects models with linear b-splines to identify inflection points, controlling for age and sex. In specialist amyotrophic lateral sclerosis clinic cases, models indicated decreasing levels of total and low-density lipoprotein cholesterol prior to an inflection point in the years before symptom onset (total cholesterol 3.25 years, low-density lipoprotein cholesterol 1.25 years), after which they stabilized or rose. A similar pattern was observed in amyotrophic lateral sclerosis cases within UK Biobank, occurring several years prior to diagnosis (total cholesterol 7 years, low-density lipoprotein cholesterol 7.25 years), differing significantly from matched controls. High-density lipoprotein cholesterol followed a similar pattern but was less robust to sensitivity analyses. Levels of triglyceride remained stable throughout. Glycated haemoglobin temporal profiles were not consistent between the clinic and biobank cohorts. Creatinine level trajectories prior to amyotrophic lateral sclerosis did not differ significantly from controls but decreased significantly in the symptomatic period after an inflection point of 0.25 years after symptom onset (clinic cohort) or 0.5 years before diagnosis (UK Biobank). These data provide further evidence for a pre-symptomatic period of dynamic metabolic change in amyotrophic lateral sclerosis, consistently associated with alterations in blood cholesterols. Such changes may ultimately contribute to biomarkers applicable to population screening and for pathways guiding the targeting of preventative therapy.